Influence of Oregano Essential Oil on the Rumen Microbiome of Organically Reared Alpine Goats: Implications for Methanobacteria Abundance - Dimitrios Kyrtsoudis; Maria V. Alvanou; Dimitrios Loukovitis; Dimitrios Gourdouvelis; Vasileios A. Bampidis; Dimitrios Chatziplis; Ioannis K. Mitsopoulos (Animals)
The present study aimed to evaluate the effects of dietary supplementation with organic oregano (Origanum vulgare) essential oil (OEO) on the rumen microbial population, with a focus on methanogenic archaea, in lactating dairy goats. A total of nine age-matched goats (mean body weight 49 ± 1.8 kg) were assigned to three experimental groups (n = 3 per group) in a completely randomized design. All animals were fed a basal diet consisting of a corn-based concentrate and a forage mix composed of alfalfa hay, wheat straw and corn silage. Group 1 was the control group while Groups 2 and 3 received an OEO supplement at dosages of 1 mL/day and 2 mL/day per animal, respectively, incorporated into the concentrate feed. Rumen fluid samples were collected on days 15, 30 and 45 of the feeding trial and their microbial profile was assessed using NGS analysis. The results demonstrated a reduction in the relative abundance of methanobacteria in both OEO-supplemented groups compared to the control group. Statistical analysis revealed significant differences between feeding groups and days of sampling. These findings suggest that OEO has the potential to modulate the rumen microbiome by reducing methane-producing archaeal populations. In conclusion, dietary supplementation with OEO may serve as a natural strategy to mitigate enteric methane emissions in Alpine dairy goats.